Organic / inorganic composite porous heat insulation film and preparation method thereof

By using the preparation method of an organic/inorganic composite porous insulation film in the porous insulation material, the combination of meta-aramid and vermiculite nanosheets is used to solve the problem that inorganic materials are difficult to disperse uniformly in polymers, and the preparation of high-performance insulation materials is realized, with multiple properties such as high temperature resistance, flame retardant, high strength, and flexibility.

CN119684668APending Publication Date: 2025-03-25INST OF LASER MFG HENAN ACAD OF SCI

Patent Information

Application Number
CN202510024219.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, inorganic materials are difficult to disperse uniformly in polymers, making it difficult to prepare high-performance thermal insulation materials, and porous thermal insulation materials are difficult to have high temperature resistance, flame retardant, high strength, and flexibility at the same time.

Method used

Using a preparation method of an organic/inorganic composite porous heat insulation film, an organic/inorganic composite porous heat insulation film is obtained by adding a pore-forming agent to a meta-aramid solution and adding a vermiculite nanosheet dispersion liquid to form an organic/inorganic mixed liquid, and then immersing it in a solidification bath through extrusion or coating on a substrate, and heating and drying it while fixing it in both directions, to obtain an organic/inorganic composite porous heat insulation film.

Benefits of technology

The high tensile strength and thermal decomposition temperature of the organic/inorganic composite porous heat insulation film are achieved, and the low thermal conductivity coefficient makes the film have high temperature resistance, high strength, flame retardant, and flexible properties, and has good heat insulation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684668A_ABST
    Figure CN119684668A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heat insulation materials, in particular to an organic / inorganic composite porous heat insulation film and a preparation method thereof. The preparation method of the organic / inorganic composite porous heat-insulating film comprises the following steps: adding a pore-forming agent into a meta-aramid solution to obtain a meta-aramid mixed solution; adding the vermiculite nanosheet dispersion liquid into the meta-aramid fiber mixed liquid to obtain an organic / inorganic mixed liquid; extruding or coating the organic / inorganic mixed solution on a substrate, and immersing the substrate in a coagulating bath to obtain organic / inorganic composite gel; and heating and drying while bidirectionally fixing the organic / inorganic composite gel to obtain the organic / inorganic composite porous heat-insulating film. The organic / inorganic composite porous heat-insulating film prepared by the preparation method of the organic / inorganic composite porous heat-insulating film has excellent performances of high temperature resistance, flame retardance, high strength, flexibility and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal insulation materials, and in particular to an organic / inorganic composite porous thermal insulation film and a preparation method thereof. Background Art

[0002] Thermal insulation materials are widely used in aerospace, industrial insulation, building energy conservation, protective clothing and other fields. High-performance thermal insulation materials have become a major national strategic need. Porous thermal insulation materials can simultaneously inhibit heat convection, heat conduction and heat radiation, and are an ideal thermal insulation system.

[0003] Porous insulation materials are mainly divided into two categories: inorganic porous insulation materials and polymer porous insulation materials. Although inorganic porous insulation materials are resistant to high temperatures, flame retardant, and applicable to a wide temperature range, they are cumbersome to prepare, difficult to process, brittle, and low in strength. Polymer porous insulation materials are easy to process, have good toughness, and high strength, but are usually not resistant to high temperatures and have poor flame retardant effects.

[0004] By combining polymer materials with inorganic materials, high-performance thermal insulation materials can be obtained by using inorganic materials to improve their thermal stability, flame retardancy and strength while retaining the advantages of polymer porous thermal insulation materials such as easy processing and good toughness. However, inorganic materials are difficult to disperse evenly in polymer materials, which affects the performance of the resulting thermal insulation materials. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an organic / inorganic composite porous thermal insulation film, which is used to solve the problem in the prior art that it is difficult to prepare high-performance thermal insulation materials because inorganic materials are difficult to disperse evenly in polymers.

[0006] The present invention also provides an organic / inorganic composite porous thermal insulation film to solve the problem in the prior art that porous thermal insulation materials are difficult to simultaneously possess properties such as high temperature resistance, flame retardancy, high strength, and flexibility.

[0007] In order to solve the above problems, the present invention proposes a method for preparing an organic / inorganic composite porous thermal insulation film, and the technical solution adopted is: A method for preparing an organic / inorganic composite porous thermal insulation film comprises the following steps: adding a pore former to a meta-aramid solution to obtain a meta-aramid mixed solution; adding a vermiculite nanosheet dispersion to the meta-aramid mixed solution to obtain an organic / inorganic mixed solution; extruding or coating the organic / inorganic mixed solution on a substrate and then immersing the solution in a coagulation bath to obtain an organic / inorganic composite gel; and heating and drying the organic / inorganic composite gel while bidirectionally fixing the organic / inorganic composite gel to obtain an organic / inorganic composite porous thermal insulation film.

[0008] The beneficial effects of the present invention are: 1) The thermal stability of the meta-aramid polymer material used in the preparation method of the organic / inorganic composite porous thermal insulation film of the present invention is better than that of most polymer materials, and the meta-aramid polymer material has high strength and good flame retardancy, and the selected inorganic material vermiculite nanosheets has excellent thermal stability and flame retardancy, and at the same time, it has good affinity with the meta-aramid; 2) The method for preparing the organic / inorganic composite porous thermal insulation film of the present invention uses a solution method to prepare the organic / inorganic composite porous thermal insulation film. The vermiculite nanosheets are uniformly dispersed in the solution and have good affinity with the meta-aramid fiber, so that the vermiculite nanosheets are uniformly dispersed in the meta-aramid fiber after film formation, thereby effectively improving the thermal stability and mechanical strength of the meta-aramid fiber; 3) The preparation method of the organic / inorganic composite porous thermal insulation film of the present invention fixes the organic / inorganic composite gel in two directions during drying, thereby reducing its shrinkage during the heating and drying process, thereby increasing the porosity, thereby obtaining a better thermal insulation effect, and at the same time orienting the molecular chains of the organic / inorganic composite porous thermal insulation film, thereby improving the mechanical strength.

[0009] In order to obtain an organic / inorganic composite porous thermal insulation film with high porosity, preferably, the pore former includes at least one of glycerol, water, ethanol, methanol, ethylene glycol, propanol, isopropanol, butanol, polyvinyl pyrrolidone, polyethylene glycol, carboxymethyl cellulose, and chitosan.

[0010] In order to simultaneously dissolve the meta-aramid and uniformly disperse the vermiculite nanosheets, preferably, the solvent of the meta-aramid solution is at least one of dimethylacetamide, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene; and the mass concentration of the meta-aramid in the meta-aramid solution is 5% to 20%.

[0011] In order to obtain an organic / inorganic composite porous thermal insulation film with a good pore structure, preferably, the mass ratio of the pore former to the meta-aramid solution is 1:(5~100).

[0012] In order to simultaneously dissolve the meta-aramid and uniformly disperse the vermiculite nanosheets, preferably, the solvent used in the vermiculite nanosheet dispersion is at least one of dimethylacetamide, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene; and the mass concentration of the vermiculite nanosheets in the vermiculite nanosheet dispersion is 0.5% to 10%.

[0013] In order to evenly disperse the vermiculite nanosheets, preferably, the mass ratio of the vermiculite nanosheet dispersion to the meta-aramid mixed solution is 1:(0.1-200).

[0014] In order to improve the pore structure of the organic / inorganic composite porous thermal insulation membrane and enhance its mechanical strength, preferably, the solvent used in the coagulation bath is at least one of glycerol, water, ethanol, methanol, ethylene glycol, propanol, isopropanol, butanol, dimethylacetamide, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene.

[0015] In order to further improve the pore structure of the organic / inorganic composite porous thermal insulation film and enhance its mechanical strength, preferably, the organic / inorganic mixed liquid is extruded or coated on a substrate and then immersed in a coagulation bath to obtain an organic / inorganic composite gel, specifically: the organic / inorganic mixed liquid is extruded or coated on a substrate and then immersed in at least one primary coagulation bath to obtain an organic / inorganic composite gel.

[0016] Further preferably, the organic / inorganic mixed liquid is extruded or coated on the substrate and then immersed in a coagulation bath to obtain an organic / inorganic composite gel, specifically: the organic / inorganic mixed liquid is extruded or coated on the substrate and then immersed in a three-stage coagulation bath to obtain an organic / inorganic composite gel.

[0017] In order to further improve the pore structure of the organic / inorganic composite porous thermal insulation membrane, preferably, the heating and drying temperature is 30~200 °C and the time is 0.5~48 h.

[0018] The present invention also proposes an organic / inorganic composite porous thermal insulation film, the technical solution adopted is: An organic / inorganic composite porous thermal insulation film is prepared by the above-mentioned method for preparing the organic / inorganic composite porous thermal insulation film.

[0019] The beneficial effects of the present invention are as follows: the organic / inorganic composite porous thermal insulation film prepared by the preparation method of the organic / inorganic composite porous thermal insulation film of the present invention has high tensile strength and thermal decomposition temperature, and low thermal conductivity, so that the organic / inorganic composite porous thermal insulation film is resistant to high temperature, high in strength, flame retardant, flexible, and has good thermal insulation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the organic / inorganic composite porous thermal insulation film prepared in Example 1 of the method for preparing the organic / inorganic composite porous thermal insulation film of the present invention; Figure 2 This is a SEM image of the organic / inorganic composite porous thermal insulation film prepared in Example 2 of the method for preparing the organic / inorganic composite porous thermal insulation film of the present invention; Figure 3 This is a SEM image of the organic / inorganic composite porous thermal insulation membrane prepared in Example 3 of the method for preparing the organic / inorganic composite porous thermal insulation membrane of the present invention. DETAILED DESCRIPTION

[0021] In the prior art, it is difficult to prepare high-performance thermal insulation materials because inorganic materials are difficult to disperse uniformly in polymers. The present invention provides a method for preparing an organic / inorganic composite porous thermal insulation film, comprising the following steps: adding a pore-forming agent to a meta-aramid solution to obtain a meta-aramid mixed solution; adding a vermiculite nanosheet dispersion to the meta-aramid mixed solution to obtain an organic / inorganic mixed solution; extruding or coating the organic / inorganic mixed solution on a substrate and then immersing it in a coagulation bath to obtain an organic / inorganic composite gel; and heating and drying the organic / inorganic composite gel while bidirectionally fixing it to obtain an organic / inorganic composite porous thermal insulation film.

[0022] The technical concept of the present invention is: the thermal stability of meta-aramid is better than that of most polymer materials, and the meta-aramid has high strength and good flame retardancy. At the same time, vermiculite nanosheets have excellent thermal stability and flame retardancy, and have good affinity with meta-aramid; a pore-forming agent is added to the meta-aramid solution to improve the porosity after film formation; in order to uniformly disperse the vermiculite nanosheets in the meta-aramid after film formation, the vermiculite nanosheet dispersion is added to the meta-aramid mixed solution to obtain an organic / inorganic mixed solution; the organic / inorganic mixed solution is extruded or coated on a substrate, and in order to improve the pore structure of the organic / inorganic composite porous thermal insulation film and improve its mechanical strength, it is immersed in a coagulation bath to obtain an organic / inorganic composite gel; in order to further improve the porosity and mechanical strength of the organic / inorganic composite porous thermal insulation film, the organic / inorganic composite gel is fixed in both directions and heated and dried to obtain an organic / inorganic composite porous thermal insulation film. The organic / inorganic composite porous thermal insulation film prepared by the method for preparing the organic / inorganic composite porous thermal insulation film of the present invention is resistant to high temperatures, has high strength, is flame-retardant, is flexible, and has good thermal insulation effect.

[0023] Specifically, the method for preparing the organic / inorganic composite porous thermal insulation film comprises the following steps: First, a pore-forming agent is added to a meta-aramid solution, and the mixture is stirred at a speed of 100-1500 rpm for 0.5-12 h to completely dissolve the pore-forming agent, thereby obtaining a meta-aramid mixed solution; wherein the pore-forming agent includes at least one of glycerol, water, ethanol, methanol, ethylene glycol, propanol, isopropanol, butanol, polyvinyl pyrrolidone, polyethylene glycol, carboxymethyl cellulose, and chitosan; the solvent of the meta-aramid solution is at least one of dimethylacetamide, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene; the mass concentration of the meta-aramid in the meta-aramid solution is 5-20%; and the mass ratio of the pore-forming agent to the meta-aramid solution is 1:(5-100).

[0024] Secondly, a vermiculite nanosheet dispersion is added to the meta-aramid mixture, and the mixture is stirred at a speed of 100-1500 rpm for 0.5-12 h to obtain an organic / inorganic mixture; wherein the solvent used for the vermiculite nanosheet dispersion is at least one of dimethylacetamide, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene; the mass concentration of vermiculite nanosheets in the vermiculite nanosheet dispersion is 0.5-10%; and the mass ratio of the vermiculite nanosheet dispersion to the meta-aramid mixture is 1:(0.1-200).

[0025] Next, the organic / inorganic mixed liquid is coated on a substrate, and then immersed in a coagulation bath to obtain an organic / inorganic composite gel; wherein, the organic / inorganic mixed liquid is extruded or coated on a substrate and then immersed in a coagulation bath to obtain an organic / inorganic composite gel, specifically: the organic / inorganic mixed liquid is extruded or coated on a substrate and then immersed in at least one coagulation bath to obtain an organic / inorganic composite gel, and the solvent used in the coagulation bath is at least one of glycerol, water, ethanol, methanol, ethylene glycol, propanol, isopropanol, butanol, dimethylacetamide, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene.

[0026] Finally, the organic / inorganic composite gel is fixed in both directions and heated to 30~200 °C and maintained for 0.5~48 h to finally obtain an organic / inorganic composite porous insulation film.

[0027] The implementation process of the present invention is described in detail below in conjunction with specific embodiments. However, it will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. It should also be noted that, for ease of description, only the parts related to the invention are shown in the embodiments.

[0028] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail with reference to the embodiments below.

[0029] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0030] In the following examples, among the raw materials used, the average molecular weight of meta-aramid is 80,000, the thickness of vermiculite nanosheets is less than 5 nm, and the size is 0.5-1 μm, and the remaining raw materials are common commercial products that can be directly purchased or can be prepared according to conventional techniques in the art.

[0031] 1. Specific embodiments of the method for preparing the organic / inorganic composite porous thermal insulation film of the present invention Example 1 The method for preparing the organic / inorganic composite porous thermal insulation film provided in this embodiment comprises the following steps: First, 4 g of glycerol was added to 20 g of a 20% m-aramid dimethylacetamide solution, and the mixture was stirred at 1500 rpm for 0.5 h to completely dissolve the pore-forming agent, thereby obtaining a m-aramid mixed solution. Secondly, 240 g of a 0.5% concentration of vermiculite nanosheet dispersion containing dimethylacetamide as solvent was added to 24 g of the meta-aramid mixed solution, and the mixture was stirred at 100 rpm for 12 h to obtain an organic / inorganic mixed solution. Next, the organic / inorganic mixed solution is coated on a substrate, first immersed in a solution of glycerol and dimethylacetamide in a volume ratio of 3:7, then immersed in a solution of dimethylacetamide and water in a volume ratio of 3:7, and then immersed in water to obtain an organic / inorganic composite gel; Finally, the organic / inorganic composite gel was fixed in both directions and heated to 200 °C and maintained for 0.5 h to finally obtain an organic / inorganic composite porous insulation film.

[0032] Example 2 First, 0.2 g of water was added to 20 g of a 5% m-aramid dimethylacetamide solution, and the mixture was stirred at 100 rpm for 12 h to completely dissolve the pore-forming agent, thereby obtaining a m-aramid mixed solution. Secondly, 0.1 g of a 10% mass concentration of vermiculite nanosheet dispersion with dimethylacetamide as solvent was added to 20.2 g of the meta-aramid mixed solution, and the mixture was stirred at 1500 rpm for 0.5 h to obtain an organic / inorganic mixed solution. Next, the organic / inorganic mixed solution is coated on a substrate, first immersed in a solution of dimethylacetamide and water in a volume ratio of 7:3, and then immersed in ethanol to obtain an organic / inorganic composite gel; Finally, the organic / inorganic composite gel was fixed in both directions and heated to 30 °C for 48 h to obtain an organic / inorganic composite porous insulation film.

[0033] Example 3 First, 0.5 g of polyvinyl pyrrolidone was added to 20 g of a 10% mass concentration of meta-aramid dimethylacetamide solution, and stirred at 1000 rpm for 6 h to completely dissolve the pore-forming agent to obtain a meta-aramid mixed solution. Secondly, 2 g of a 5% concentration of vermiculite nanosheet dispersion with dimethylacetamide as solvent was added to 20.5 g of the meta-aramid mixed solution, and the mixture was stirred at 1000 rpm for 3 h to obtain an organic / inorganic mixed solution. Next, the organic / inorganic mixed solution is squeezed onto a substrate and then immersed in water to obtain an organic / inorganic composite gel; Finally, the organic / inorganic composite gel was fixed in both directions and heated to 120 °C and maintained for 10 h to finally obtain an organic / inorganic composite porous insulation film.

[0034] In the present application, when the pore-forming agent includes at least one of ethanol, methanol, ethylene glycol, propanol, isopropanol, butanol, polyethylene glycol, carboxymethyl cellulose, and chitosan, the technical effect obtained is the same as the technical effect of the above embodiment.

[0035] In the present application, when the solvent of the meta-aramid solution is at least one of dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene, the technical effect obtained is the same as the technical effect of the above embodiment.

[0036] In the present application, when the solvent used for the vermiculite nanosheet dispersion is at least one of dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene, the technical effect obtained is the same as that of the above embodiment.

[0037] In the present application, when the solvent used in the coagulation bath is at least one of methanol, ethylene glycol, propanol, isopropanol, butanol, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene, the technical effect obtained is the same as the technical effect of the above embodiment.

[0038] 2. Experimental Examples Experimental Example 1 The cross-sectional morphology of the organic / inorganic composite porous thermal insulation film prepared by the preparation method of the organic / inorganic composite porous thermal insulation film of the above-mentioned Examples 1-3 was tested. Specifically, the cross-sectional morphology of the sample was characterized by using a scanning electron microscope with an acceleration voltage of 10 kV. The test results are as follows: Figure 1 , Figure 2 and Figure 3It can be seen that in the SEM images of the organic / inorganic composite porous thermal insulation film prepared by the method for preparing the organic / inorganic composite porous thermal insulation film of Examples 1-3, there are a large number of uniform pore structures, and the vermiculite nanosheets are uniformly dispersed in the meta-aramid matrix, indicating that the organic / inorganic composite porous thermal insulation film prepared by the method for preparing the organic / inorganic composite porous thermal insulation film of the present application has a high porosity and a good thermal insulation effect.

[0039] Experimental Example 2 The organic / inorganic composite porous thermal insulation film prepared by the preparation method of the organic / inorganic composite porous thermal insulation film of the above Examples 1-3 was subjected to tensile strength, thermal weight loss and thermal conductivity tests. Specifically, for tensile strength, an electronic universal testing machine was used to test the tensile strength of the sample, with a tensile speed of 1 mm / min and an initial spacing of 10 cm. For thermal decomposition temperature, a thermal weight loss curve of the sample was tested using a thermal gravimetric analyzer, and the thermal decomposition temperature of the sample was obtained from the curve. The test was carried out in a nitrogen atmosphere with a heating rate of 10 °C min -1 , temperature range 30~800 °C. Thermal conductivity, thermal conductivity of the sample was tested using a thermal constant analyzer. The specific results are shown in Table 1: Table 1 Performance comparison of organic / inorganic composite porous thermal insulation films prepared in Examples 1-3

[0040] It can be seen from Table 1 that the tensile strength of the organic / inorganic composite porous thermal insulation film prepared by the preparation method of the organic / inorganic composite porous thermal insulation film of Examples 1-3 is above 14.0 MPa, and the highest is 20.5 MPa. The thermal decomposition temperature of the organic / inorganic composite porous thermal insulation film prepared by Examples 1-3 is above 429 °C, and the highest is 436 °C. The thermal conductivity of the organic / inorganic composite porous thermal insulation film prepared by Examples 1-3 is 0.143 W m -1 K -1 Below, the minimum is 0.122 W m -1 K -1 .

[0041] This shows that the organic / inorganic composite porous thermal insulation film prepared by the preparation method of the organic / inorganic composite porous thermal insulation film provided in the present application has high tensile strength and thermal decomposition temperature, as well as low thermal conductivity, and is a high-performance thermal insulation material.

[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an organic / inorganic composite porous thermal insulation film, characterized in that: The following steps are involved: A pore-forming agent is added to a meta-aramid solution to obtain a meta-aramid mixed solution; a vermiculite nanosheet dispersion is added to the meta-aramid mixed solution to obtain an organic / inorganic mixed solution; the organic / inorganic mixed solution is extruded or coated on a substrate and then immersed in a coagulation bath to obtain an organic / inorganic composite gel; the organic / inorganic composite gel is fixed in both directions while being heated and dried to obtain an organic / inorganic composite porous thermal insulation film.

2. The method for preparing the organic / inorganic composite porous thermal insulation film according to claim 1, characterized in that: The pore-forming agent is at least one of glycerol, water, ethanol, methanol, ethylene glycol, propanol, isopropanol, butanol, polyvinyl pyrrolidone, polyethylene glycol, carboxymethyl cellulose and chitosan.

3. The method for preparing the organic / inorganic composite porous thermal insulation film according to claim 1, characterized in that: The solvent of the meta-aramid solution is at least one of dimethylacetamide, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene; and the mass concentration of the meta-aramid in the meta-aramid solution is 5% to 20%.

4. The method for preparing the organic / inorganic composite porous thermal insulation film according to claim 1, characterized in that: The mass ratio of the pore former to the meta-aramid solution is 1:(5-100).

5. The method for preparing the organic / inorganic composite porous thermal insulation film according to claim 1, characterized in that: The solvent used in the vermiculite nanosheet dispersion is at least one of dimethylacetamide, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene and benzene; the mass concentration of the vermiculite nanosheets in the vermiculite nanosheet dispersion is 0.5%-10%.

6. The method for preparing the organic / inorganic composite porous thermal insulation film according to claim 1, characterized in that: The mass ratio of the vermiculite nanosheet dispersion to the meta-aramid mixed solution is 1:(0.1-200).

7. The method for preparing the organic / inorganic composite porous thermal insulation film according to claim 1, characterized in that: The solvent used in the coagulation bath is at least one of glycerol, water, ethanol, methanol, ethylene glycol, propanol, isopropanol, butanol, dimethylacetamide, dimethyl sulfoxide, dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, dichloromethane, acetone, toluene, xylene, and benzene.

8. The method for preparing the organic / inorganic composite porous thermal insulation film according to claim 7, characterized in that: The organic / inorganic mixed liquid is extruded or coated on the substrate and then immersed in a coagulation bath to obtain the organic / inorganic composite gel. Specifically, the organic / inorganic mixed liquid is extruded or coated on the substrate and then immersed in at least one level of coagulation bath to obtain the organic / inorganic composite gel.

9. The method for preparing the organic / inorganic composite porous thermal insulation film according to claim 1, characterized in that: The heating and drying temperature is 30-200 °C and the time is 0.5-48 h.

10. An organic / inorganic composite porous thermal insulation film, characterized in that: The organic / inorganic composite porous thermal insulation film is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-temperature-resistant aramid fiber lithium ion battery composite separation membrane and preparation method thereof

    CN107170942A

  • Modified aramid polymer, aramid membrane casting solution, lithium battery diaphragm, preparation methods and lithium battery

    CN112538162A

  • Organic-inorganic composite spongy porous diaphragm as well as preparation method and application thereof

    CN119236697A

  • Porous composite organic-inorganic diaphragm, preparation method of porous composite organic-inorganic diaphragm, electrolytic hydrogen production device and application of porous composite organic-inorganic diaphragm

    CN121204736A

Cited By

  • Lithium ion battery diaphragm containing vermiculite nanosheets, preparation method of lithium ion battery diaphragm and lithium ion battery

    CN121149576A